Association between benzodiazepine anxiolytic polypharmacy and concomitant psychotropic medications in Japan: a retrospective cross-sectional study - Takeshima, Masahiro; Yoshizawa, Kazuhisa; Ogasawara, Masaya; Kudo, Mizuki; Itoh, Yu; Ayabe, Naoko; Shibata, Nana; Mishima, Kazuo (Frontiers in Psychiatry, 2024)
Introduction Guidelines for various psychiatric disorders recommend short-term use of benzodiazepine anxiolytic monotherapy in few cases. Contrarily, benzodiazepine anxiolytic polypharmacy (BAP) is not recommended in any case. However, BAP is often used in real world. Therefore, this study aimed to determine the association between BAP and concomitant use of psychotropic medications. Method This retrospective cross-sectional study used claims data from the Japan Medical Data Center. Medical information of health insurance subscribers treated with benzodiazepine anxiolytics in June 2019 was extracted. Prescription of two or more benzodiazepine anxiolytics was defined as BAP. Binary logistic regression analysis was performed to investigate the factors associated with BAP, using age group, sex, type of subscriber, and number of concomitant hypnotics, antidepressants, and antipsychotics (none, one, and two or more) as covariates. Result The eligible participants were 104,796 adults who were prescribed benzodiazepine anxiolytics. Among them, 12.6% were prescribed two or more drugs. Logistic regression analysis revealed that BAP was significantly associated with those who received hypnotic monotherapy (adjusted odds ratio [aOR]: 1.04, 95% confidence interval [CI]: 1.001–1.09, p=0.04), antidepressant monotherapy and polypharmacy (aOR: 1.57, 95% CI: 1.51–1.63, p<0.001 and aOR: 1.98, 95% CI: 1.88–2.09, p<0.001, respectively), and antipsychotic monotherapy and polypharmacy (aOR: 1.12, 95% CI: 1.07–1.19, p<0.001 and aOR: 1.41, 95% CI: 1.30–1.54, p<0.001, respectively). Conversely, lower BAP was associated with those who received hypnotic polypharmacy (aOR: 0.86, 95% CI: 0.81–0.91, p<0.001). Discussion This study showed that the greater the number of concomitant antidepressants and antipsychotics, the greater the association with BAP. Since combination therapy with antidepressants or antipsychotics is generally not recommended, patients receiving combination therapy with these medications may be resistant to pharmacotherapy. Therefore, implementing the recommended non-pharmacological treatments may reduce BAP.